(untitled) (Journal of Medical & Health Sciences Review, 2025)
Calcium oxalate (CaOx) stones appear as the prevalent type of kidney stones which collectively form a substantial portion of the worldwide urolithiasis issue. The complete mechanisms which control the development of CaOx kidney stones have not been completely revealed by extensive research. The research analyzes CaOx stone pathophysiological mechanisms through kitchen epithelial cells (KECs) involvement in crystal adhesion while investigating inflammation and apoptosis and analyzing oxidative stress. The study examines crucial risk elements beginning with inherited tendencies and continuing with food-related factors together with metabolic dysfunctions while investigating possible treatment options. The mechanisms of CaOX stone formation received evaluation through an extensive analysis of experimental studies and recent publications. The research report describes the Stone development process through observations of crystal nucleation mechanisms and monitoring of urinary pH adjustments and solution supersaturation quantities. The research specifically examines how KECs affect cellular responses to crystalline adherence together with their reaction to oxidative stress and apoptotic mechanisms. Researchers evaluate the successful preventive and therapeutic management techniques of KECs which encompass dietary adjustments alongside pharmacological therapy and forward-looking treatment approaches. CaOx stone development depends on urinary supersaturation along with crystal aggregation and how cells in the renal epithelium interact with each other. KECs actively control the development of inflammatory reactions and oxidative pressure together with apoptosis pathways to influence stone formation. The metabolism of oxalate along with calcium control and oxalate regulation experience influence from inherited risk factors eating patterns and gut microbial activity. The prevention of stone recurrence becomes possible through three key methods including fluid consumption boost and restrictive oxalate diets along with probiotic treatments.